Theory and practice of forming the management culture of future primary school teachers - Adanov, K.B. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the monograph, the formation of the management culture of future primary school teachers in the process of vocational training is considered from the perspective of pedagogical management. Intended for students, candidates for a master’s degree, PhD students, researchers, as well as practitioners.
Keywords: management culture; primary school; teachers; vocational training; future